A novel approach of core-shell Ag@Pt nanoparticles production - Chowdhury, Silvia; Yusof, Faridah; Sulaiman, Nadzril; Faruck, Mohammad Omer (Trans Tech Publications, Switzerland, 2017)
Pt-based nanoparticles (NPs) have numerous applications, such as, as catalyst, in car exhaust systems, gas sensors, biosensors and cancer therapy. One of the Pt based NPs which has been successfully produced is core-shell Ag@Pt NPs. Numerous methods for the synthesis of this material have been reported. This paper reports a fully new approach of chemical mediated synthesis for core-shell Ag@Pt NPs. Characterization process for the synthesized Ag@Pt NPs, carried out by the UV-vis Spectroscopy, Transmission Electron Microscopy (TEM), High Resolution Transmission Electron Microscopy (HRTEM) showed that the core AgNPs have approximate sizes of 18 nm in diameter are shelled with Pt and the sizes of core-shell Ag@Pt NPs were estimated to be around 29 nm in diameter.